LINGUISTIC FEATURES OF INDONESIAN ENGLISH: EVIDENCE FROM PEDIATRICIANS, TVRI BROADCASTERS, AND WAITRESSES - Maneba, Sanaria; Hanafiah, Waode; Adu, Baharudin; Syafitri, Nining (English Education Journal, 2025)
This research investigates the linguistic features of English variety used by Indonesian speakers in professional settings, specifically among pediatricians, South Sulawesi TVRI broadcasters, and waitresses. The research addresses how occupational background and first language influence the use of English in spoken interactions. Employing a qualitative descriptive approach, data were collected through recorded interviews with seven participants from the three professions. The analysis focused on phonological, lexical, and syntactic features, revealing a range of linguistic phenomena such as vowel shifts, glottal stops, and code-switching, which reflect both regional accents and the speakers' social contexts. Notably, pediatricians showed phonological transfer from regional languages like Butonese and Buginese, while broadcasters demonstrated lexical borrowing and occasional formal register inconsistency. Waitresses exhibited simpler sentence structures with noticeable pronunciation influences from their vernaculars. The findings highlight how English spoken by Indonesian professionals is shaped not only by linguistic competence but also by sociolinguistic variables such as occupation, regional origin, and communicative purpose. This research contributes to the understanding of World Englishes and emphasizes the importance of sociolinguistic awareness in teaching and evaluating English proficiency in multilingual societies.